2020
DOI: 10.1098/rsbl.2020.0075
|View full text |Cite
|
Sign up to set email alerts
|

High-Arctic family planning: earlier spring onset advances age at first reproduction in barnacle geese

Abstract: Quantifying how key life-history traits respond to climatic change is fundamental in understanding and predicting long-term population prospects. Age at first reproduction (AFR), which affects fitness and population dynamics, may be influenced by environmental stochasticity but has rarely been directly linked to climate change. Here, we use a case study from the highly seasonal and stochastic environment in High-Arctic Svalbard, with strong temporal trends in breeding conditions, to test whether rapid climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Due to the relatively small sample size we used, all of the five goslings in the mining group were male, showing significantly higher hemolysis titers than the other two groups. Thus, although the goslings we used in the current study were at an early stage of development and much younger than the age for sexual maturity (2 years of age), , our results demonstrated that sex instead of Hg exposure was the major driver of the differences in the hemolysis titer.…”
Section: Resultsmentioning
confidence: 55%
“…Due to the relatively small sample size we used, all of the five goslings in the mining group were male, showing significantly higher hemolysis titers than the other two groups. Thus, although the goslings we used in the current study were at an early stage of development and much younger than the age for sexual maturity (2 years of age), , our results demonstrated that sex instead of Hg exposure was the major driver of the differences in the hemolysis titer.…”
Section: Resultsmentioning
confidence: 55%
“…While we do not have data to explore whether the onset or rate of premigratory fueling has been subject to change in recent years, no advances in migration departure have been observed for barnacle geese ( Tombre et al 2008 ; Eichhorn et al 2009 ; Lameris et al 2018 ). Optimal conditions for reproduction in the Arctic breeding grounds are generally advancing ( Lameris et al 2018 ; Fjelldal et al 2020 ), but large annual stochasticity in the onset of spring ( Box et al 2019 ; Lameris et al 2019 ), as well as contrasting effects of earlier springs on early and late stages of reproduction ( Nolet et al 2020 ), may not yet drive geese to advance their migratory departure from the wintering grounds. Nevertheless, in contrast to barnacle geese, which currently use few temperate staging sites and almost make a “jump” migration to the Arctic coast ( Eichhorn et al 2009 ), larger species that use a chain of temperate and Arctic stopover sites have in recent decades advanced their migration departure ( Nuijten et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fledged brood size ( fec ) describes the number of fledglings per mother, fitted as a Poisson response. We included observations from 2 year‐olds onwards (age of sexual maturity, Forslund and Larsson, 1992; Fjelldal et al ., 2020) in the reproductive models, and only successfully reproducing individuals ( R = 1) in the model of fec . We fitted all (G)LMM’s with year as a random effect using the package lme4 in R (Bates et al ., 2015).…”
Section: Methodsmentioning
confidence: 99%